PETITION TO INITIATE RULEMAKING TO AMEND FEDERAL AVIATION REGULATIONS: CERTIFICATION AND OPERATION (Tufts Archival Research Center, 2007)
Marginalia; Report presented by the R.J. Reynolds Tobacco Company in response to a petition against smoking on U.S. aircraft carriers presented by various flight attendant unions via the Federal Aviation Administration (FAA). Argues that the FAA should not interfere with Congressional rulings on smoking restrictions. Reviews epidemiologic data and risk assessment stating that levels of environmental tobacco smoke (ETS) are low in aircraft cabins. Addresses fire safety concerns. Concludes that the FAA should deny the petition.